2020
DOI: 10.1177/0846537120939930
|View full text |Cite
|
Sign up to set email alerts
|

Initial Canadian Experience of Prostate Artery Embolization for Symptomatic Benign Prostatic Hyperplasia: Midterm Outcomes

Abstract: Introduction: This study aimed to assess the midterm outcomes and safety of prostate artery embolization (PAE) for the treatment of benign prostatic hyperplasia (BPH). Methods: A single-center, retrospective review of PAE performed for BPH was performed. Validated International Prostate Symptom Score (IPSS), quality of life (QoL) index, and International Index for Erectile Function (IIEF-5) questionnaires were completed at baseline and at least 12 months post-procedure. Prostate imaging was performed preproced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…22,25 Third, the choice between RAA and FAA was left to the operator preference, which might have introduced bias due to selection of one approach over the other in light of patients' specificities, and limited the generalizability of our results. 33 Finally, we did not assess the differences in local pain at the puncture site between the two approaches. 34 In conclusion, the results of this study suggest that for patients with HCC, RAA is a safe approach that does not compromise the technical efficacy of TACE compared with FAA, in particular regarding the selectivity of the embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,25 Third, the choice between RAA and FAA was left to the operator preference, which might have introduced bias due to selection of one approach over the other in light of patients' specificities, and limited the generalizability of our results. 33 Finally, we did not assess the differences in local pain at the puncture site between the two approaches. 34 In conclusion, the results of this study suggest that for patients with HCC, RAA is a safe approach that does not compromise the technical efficacy of TACE compared with FAA, in particular regarding the selectivity of the embolization.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 Third, the choice between RAA and FAA was left to the operator preference, which might have introduced bias due to selection of one approach over the other in light of patients’ specificities, and limited the generalizability of our results. 33 Finally, we did not assess the differences in local pain at the puncture site between the two approaches. 34…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous retrospective or prospective case series from multiple international sites demonstrating the efficacy of PAE for the treatment of LUTS [ 3 , 40 , 61 , 62 , 63 , 64 , 65 ]. There were slight variations in methodology and follow up per study, but each demonstrated good clinical outcomes overall.…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic artery embolization (PAE) has emerged as a minimally invasive therapy for symptomatic patients due to BPH and as an alternative to TURP, with similar clinical outcomes, fewer complications, and shorter recovery time [3][4][5][6][7][8][9]. The National Institute for Health and Care Excellence (NICE) supports the use of PAE for LUTS secondary to BPH, provided that standard arrangements are in place for clinical management, consent and audit [10].…”
Section: Introductionmentioning
confidence: 99%